Genome structure of introgressive lines Triticum aestivum/Aegilops sharonensis - Antonyuk, M.Z.; Bodylyova, M.V.; Ternovskaya, T.K. (Цитология и генетика, 2009)
The lines Triticum aestivum/Aegilops sharonensis were explored in regard to the presence of introgressions in the line genomes, their amount and belonging to definite homoeologic group. The results of studying of chromosome associations in M1 of pollen mother celles in the hybrids between the lines with each other and with recurrent common wheat genotype Avrora were compared with the data of the line assessment for the chromosomal biochemical and morphological markers. 26 lines were distinguished between six groups with specific genome rearrangement regard to recurrent genotype. Линии Triticum aestivum/Aegilops sharonensis изучены относительно количества и гомеологической принадлежности интрогрессий в их геноме. Метод анализа–сопоставление данных изучения хромосомных ассоциаций в М1 материнских клеток пыльцы линий и их гибридов F1 друг с другом и с рекуррентным генотипом мягкой пшеницы Аврора, а также результатами оценки линий по хромосомоспецифическим биохимическим и морфологическим маркерным признакам. 26 изученных линий отнесены к шести разным группам с характерными перестройками генома относительно рекуррентного генотипа. Лінії Triticum aestivum/Aegilops sharonensis вивчено стосовно кількості та гомеологічної належності інтрогресій в їх геномі. Метод аналізу – зіставлення даних вивчення хромосомних асоціацій у М1 материнських клітин пилку ліній та їх гібридів F1 одна з одною та з рекурентним генотипом м’якої пшениці Аврора, а також результатів оцінки ліній за хромосомоспецифічними біохімічними та морфологічними маркерними ознаками. 26 вивчених ліній віднесено до шести різних груп з характерними перебудовами геному стосовно рекурентного генотипу.